Hypofractionated stereotactic radiotherapy for large vestibular schwannomas and the impact of pre-radiation debulking surgery on dosimetry and clinical outcomes. (6th March 2023) - Mallory, Matthew; Kauweloa, Kevin; Staecker, Hinrich; Camarata, Paul; Chamoun, Roukoz; Neeranjun, Rishi; Badkul, Rajeev; TenNapel, Mindi; Shelton, Shary; Wang, Fen
Abstract: Introduction: This study was aimed to evaluate the outcomes of patients with large (>2 cm in great diameter) vestibular schwannomas (VSs) treated with hypofractionated stereotactic radiotherapy (HFSRT) compared to small (<2 cm) ones and the impact of debulking surgery prior to radiation for large VSs. Methods: Fifty-nine patients with VSs treated with HFSRT (25 Gy in 5 fractions) were evaluated by tumour size and surgical status. Patients were divided based on tumour size: small VSs ( n = 42) and large VSs ( n = 17). The large group was further divided into the groups of pre-treatment debulking surgery ( n = 8) and no surgery ( n = 9). Rates of tumour control, brainstem necrosis and neurologic dysfunction were assessed following treatment. Pre-surgical magnetic resonance imaging (MRI) were used to generate hypothetical HFSRT plans to compare the effect of debulking surgery on dosimetry. Normal tissue complication probability (NTCP) modelling was performed to compare toxicity probabilities with and without surgical debulking in large VSs. Results: There was no statistical difference of tumour control rate between small and large VSs with 100% for small tumours and 94·1% for large tumours ( p = 0·12), respectively. In large VSs patient, the tumour control rate of HFSRT was 100% (8/8) for surgically debulked patients and 89% (8/9) for non-surgically debulked patients ( p = 0·35). There were no patients who experienced brainstem necrosis or progression of facial and trigeminal nerve symptoms after HFSRT in the entire groups of patients. Surgical debulking large VSs did not change the maximum point dose of brainstem ( p = 0·98), but significantly decreased volumes of VSs and changed the minimum dose to the hottest 0·5 cc of tumour ( p = 0·016) as well as the volume receiving at least 23 Gy ( p = 0·023). NTCP modelling revealed very low rates (average < 1%) of brainstem toxicity with or without surgical debulking, but there was a significant difference favoring surgery ( p < 0·05). Conclusions: HFSRT is a safe and effective treatment for both small and large VSs and is a viable option for patients with large VSs who cannot undergo surgery, if NTCP of pre-debulking HFSRT dosimetry is lower.